The calculation of point quantity for lighting based on android OS using ionic framework and rule based expert system - Mufadhol Mufadhol; Budi Hartono; Sulartopo Sulartopo; Maya Utami Dewi; Danang Danang; Guruh Aryotejo (Institute of Advanced Engineering and Science, 2021)
At this time, the Covid-19 pandemic has not been finished so all activities and expenditure of funds must be economical. On the each building will be required electricity resources as a means for lighting the room. Reduced activities carried out outside the room make people carry out activities indoors, this results in a significant increase in electricity consumption for lighting. PT. PLN as the provider in Indonesia of electricity services for the community experiences a shortage of electricity resources and most of the electricity resources are used for lighting purposes. Indonesia as a developing country has a very large of population growth, so it requires many buildings as a place to live or a place of business and other activities. This paper will be discussion how a smartphone with an Android operating system can be used to determining the lighting requirements using the Ionic Framework and Rule Based Expert Systems. Using this application system, so electricity to lighting can be optimal and not too wasteful, which in turn can save on the use of electrical energy resources and can save of the cost.